2016
DOI: 10.1063/1.4960264
|View full text |Cite
|
Sign up to set email alerts
|

Role of metal oxide nanostructures in extracellular pH regulations

Abstract: Abstract. A research area of great promise is the cancer treatment by regulating microenvironmental parameters of tumor cells using MgO and AlOOH. Magnesium hydroxide and aluminum oxyhydroxide (boehmite) are in the form of nanoplates and nanosheets. The morphology, structure, phases and electrokinetic properties of synthesized samples are analyzed using complex physical and chemical methods. We study how the pH of the culture medium-different when in contact with synthesized nanoplates-affects the viability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently it has been experimentally found that the low-dimensional aluminum oxyhydroxide is prospective nanomaterial (AlOOH-NM), at least, to be adjuvant in anticancer therapy [9,10]. The mechanism of AlOOH-NM antitumor activity may be provided by the oxyhydroxide influence on pH of extracellular media [11,12] or/and by probable violations in the cell membrane structure accompanied by membrane protein dysfunction, as well as by facilitating cellular uptake of the therapeutic agents, or something fourth. In any case, it is under-explored so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been experimentally found that the low-dimensional aluminum oxyhydroxide is prospective nanomaterial (AlOOH-NM), at least, to be adjuvant in anticancer therapy [9,10]. The mechanism of AlOOH-NM antitumor activity may be provided by the oxyhydroxide influence on pH of extracellular media [11,12] or/and by probable violations in the cell membrane structure accompanied by membrane protein dysfunction, as well as by facilitating cellular uptake of the therapeutic agents, or something fourth. In any case, it is under-explored so far.…”
Section: Introductionmentioning
confidence: 99%